Aerobics Development at Gymnasiums in Semarang - Darmawan, Agus (Media Ilmu Keolahragaan Indonesia, 2013)
The main purpose of this research is to detect the extent to which the organization structure, practice program, facilities and infrastructure, funding, and another supported factors that exist at gymnasiums in Semarang. This is a quantitative research. The data are collected directly by: (1) observation, (2) interview, and (3) documents collecting. The result of the research has shown that: there is a good management structure at St. Anna gymnasium, the practice program is general aerobic, types of the aerobics is the high impact and low impact aerobic, inadequate facilities and infrastructure, funding is managed by the owner of the gymnasium and has already got a fund help from the department of education of Semarang, it located at the strategic place, and already got a good support from the department. There is a good management structure at Tantia and Athalia gymnasium, the practice program are low impact and high impact aerobic, inadequate facilities and infrastructure, funding is managed by the owner of the gymnasium, it located at the strategic place, and already got a good support from the department.